2020
DOI: 10.1039/c9nr08672b
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-driven annihilation and creation of magnetic vortices in Ni discs

Abstract: Using PEEM to image ferromagnetism in polycrystalline Ni disks, and ferroelectricity in their single-crystal BaTiO3 substrates, we find that voltage-driven 90° ferroelectric domain switching serves to annihilate magnetic vortices via uniaxial compressive strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Further reports on strain-mediated effects include electric-field controlled motion of magnetic domain walls around the circumference of magnetic ring structures on PMN-PT [265,266] and electric-field tuning of the chirality of magnetic vortex walls in Ni/PMN-PT [267]. Other non-collinear spin structures such as vortices have been manipulated by electric fields in Ni nanodisks on PMN-PT [268,269]. Particularly interesting is the prospect of electric-field control of topologically protected magnetic skyrmions which, because of their small size and stability, are a promising candidate as information carrier in future spintronics devices.…”
Section: Electric-field Control Of Magnetismmentioning
confidence: 99%
“…Further reports on strain-mediated effects include electric-field controlled motion of magnetic domain walls around the circumference of magnetic ring structures on PMN-PT [265,266] and electric-field tuning of the chirality of magnetic vortex walls in Ni/PMN-PT [267]. Other non-collinear spin structures such as vortices have been manipulated by electric fields in Ni nanodisks on PMN-PT [268,269]. Particularly interesting is the prospect of electric-field control of topologically protected magnetic skyrmions which, because of their small size and stability, are a promising candidate as information carrier in future spintronics devices.…”
Section: Electric-field Control Of Magnetismmentioning
confidence: 99%
“…Previous studies have shown that the strainmediated ferromagnetic/ferroelectrical (FM/FE) multiferroic heterostructure is an efficient way to realize the electric field manipulation of magnetic vortex. [8,9,[17][18][19] In such a system, the E-induced switching of FE polarization in the FE layer generates an in-plane strain, which can be transferred to the FM layer and is experimentally demonstrated to exert a significant influence on the magnetic vortex. [7,9,18] This mechanism is widely known as the strain-mediated magnetoelectric coupling (MEC) effect.…”
Section: Introductionmentioning
confidence: 99%
“…Micromagnetic simulations first predicted the possibility to switch between the magnetic vortex and polar states in FeGa nanodots grown onto a ferroelectric PZT substrate. [15] Later on, experimental works showed annihilation of magnetic vortices in Ni disks via uniaxial compressive strain transferred from PMN-PT [43] or BaTiO 3 . [44] Electric-field-assisted switching of magnetic vortex chirality was also shown in Co/PMN-PT.…”
Section: Introductionmentioning
confidence: 99%
“…This adds to other important issues of strain-mediated ME systems, such as clamping effects, mechanical fatigue, high fabrication costs (in the case of PMN-PT) or need of relatively large applied voltages (e.g., 400 V). 43 Among all converse ME effects, magneto-ionics is gaining attention because voltage-driven ion transport between the magnetic material of interest and an ion source/sink allows for a stringent non-volatile control of interfacial magnetism to an unprecedented extent. [25,48,49] Upon electrolyte gating, the ions may form diffusion channels or even uniform migration fronts (eventually developing new interfaces within the actuated films), resulting in unique magnetic characteristics (in e.g., oxides or nitrides).…”
Section: Introductionmentioning
confidence: 99%